Sensory attributes, physico-chemical and cooking quality of pasta formulated with durum wheat semolina and refined wheat flour - Namrata; Kumar , Shiv (Journal of Postharvest Technology, 2024)
Italian-style pasta is rarely made with soft wheat flour since it is of inferior quality than durum wheat. The market is gradually moving away from utilizing durum wheat to manufacture pasta as durum wheat is more expensive than other varieties of wheat. In this study, conventional ingredients i.e. Durum Wheat Semolina (DWS) and Refined Wheat flour (RWF) were used for preparation of pasta in alone and in-combination in different ratio & also examined for their effect on the pasta quality. Initially conventional pasta was prepared by using DWS (100%) alone which was altered simultaneously with different ratio of RWF i.e. 90:10, 80:20, 70:30, and 60:40%. The best resulted ratio was further examined for various quality parameters. In order of organoleptic aspects, sensory quality of formulated Pasta samples were evaluated on the basis of 9- point hedonic scale. It was observed that Pasta sample prepared with DWS: RWF (70:30) ratio scored more acceptability from semi-trained panellist in comparison to other treatments. This ratio was further tested for various physico-chemical properties & cooking quality parameters. On the basis of results obtained, it might assumed that pasta sample prepared with DWS: RWF might be an economical approached and also have good stability while processing.